Evaluation of Children with Steroid-resistant Nephrotic Syndrome Showing Pathologic Findings of Focal Segmental Glomerulosclerosis (FSGS) after Renal Transplantation in Iranian Educational Medical Centers from 1998 to 2018 - Ghassemi, Khadijeh; Hooman, Nakysa; Montazeri, Sahar (Journal of Pediatric Nephrology, 2018)
Introduction: Steroid resistant nephrotic syndrome due to idiopathic focal segmental glomerulosclerosis (FSGS) or genetic mutations is one of the most common causes of end-stage renal disease (ESRD) that leads to renal transplantation. The relapse of the disease in the transplanted kidney, despite proper therapeutic management pre and post transplantation, may result in graft loss. Lack of accurate data about the status of transplanted patients due to FSGS encouraged us to obtain data from all pediatric nephrologists in Iran to achieve better pre and post transplantation therapeutic management. Material and Methods: The personal data of the pediatric nephrologist as well as the data of surgical and medical management prior to transplantation, relapse in the allograft kidney, and the therapeutic response rate after relapse were collected via a questionnaire. Results: Of 82 cases of FSGS from 1998 to 2018, 23 had relapse, mostly within 1 year after transplantation. When relapse occurred, nearly all centers used plasmapheresis and rituximab and some used angiotensin converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) in addition to immunosuppressive medications and methyl prednisolone pulse therapy. Genetic studies were done in only two centers and there was no difference in immunosuppressive medications between these two centers and the idiopathic group. Pre-transplant plasmapheresis and rituximab were administered in four centers, while two centers used IVIG and one center only used plasmapheresis. Delayed graft function (DGF) was negative in 7 and positive in 9 centers. In most centers, immunosuppressive therapy consisted of a corticosteroid, mycophenolate mofetil, and tacrolimus. Relapse and recovery rates varied from less than 10% to more than 50% in all centers. Seven centers had no response to any medication. The lowest relapse rates were seen in two centers that had deceased donors and used rituximab and plasmapheresis prior to transplantation. Conclusion: It can be concluded that with regard to the possibility of relapse after transplantation and variable therapeutic management modalities before and after transplantation, it is reasonable that genetic analysis of mutations, identification of idiopathic and high-risk cases, and use of appropriate therapeutic protocols should be considered to decrease the relapse rate. Keywords: FSGS; Renal transplantation; Nephrotic syndrome; Child.